Deteksi Virus Avian Influenza H5N1 pada Anak Ayam Umur Satu Hari dengan Teknik Imunohistokimia - Setyawati, Sophia; Damajanti Soejoedono, Retno; Handharyani, Ekowati; Sumiarto, Bambang (Jurnal Veteriner; Vol 11 No 4 (2010), 2010)
Avian Influenza (AI) or bird flu caused by virus H5N1 is still present in Indonesia. The Department ofAgriculture of Indonesia has banned poultry distribution from endemic to non endemic area, except fordistribution of day old chick (DOC). The aim of this research was to detect AI virus infection in DOCdistributed from AI endemic to AI non endemic areas. Two hundred and forty DOCs from farms in WestJava and Banten were collected from Soekarno Hatta airport. Their antibody titers were examined againstAI virus by Haemaglutination Inhibition (HI) test. The AI virus detected in tissues (trachea, lung, heart,kidney, liver, and intestine) by immunohistochemistry technique. Detection of AI virus using anti AI H5N1monoclonal antibody was conducted AEC as chromogen. The result showed that 66,2% of DOC were positiveAI and 33,8% were negative AI. The 66,2% of positive samples, 43,3% showing the presence of AI antigenin trachea, lung and intestine, and 22,9% were presence in liver and kidney. DOCs were infected AI viruswith subclinical symptoms and they were potential as the source of rapid AI spread in Indonesia. It istherefore important to take a very cautious measure to prevent the spread of AI via DOC from AI endemicto free area.
Keywords: DOC, AI virus, immunohistochemistry, monoclonal antibody H5N1